Réponses

2014-04-14T23:50:19+02:00
Bonsoir,

A(t) = (2t -1)(t + 1) - 2(t + 1)
       = (t + 1) [(2t -1) - 2]
       = (t + 1) (2t -1 - 2)
       = (t + 1) (2t -3)

B(t) = (t - 4)² + ( t - 4) (2t + 3)
       = (t - 4)(t - 4) + ( t - 4) (2t + 3)
       = (t - 4) [(t - 4) + (2t + 3)]
       = (t - 4) (t - 4 + 2t + 3)
       = (t - 4) (3t - 1)

C(t) = (2t - 1)(3t + 5) + 4t(3t + 5)
       = (3t + 5) [(2t - 1) + 4t]
       = (3t + 5) (2t - 1 + 4t)
       = (3t + 5) (6t - 1)

D(t) = (5t - 1)(3t - 2) - (5t - 1)²
       = (5t - 1)(3t - 2) - (5t - 1)(5t - 1)
       = (5t - 1) [(3t - 2) - (5t - 1)]
       = (5t - 1) (3t - 2 - 5t + 1)
       = (5t - 1) (-2t - 1)